Leap motion controlled robotic arm - Lopez, Mark Joniel M.; Mamasig, Elykim T.; Marquez, Amaida Issabelle B.; Lopez, Kenneth Oliver S. (2015)
This project aimed to create an Arduino-powered Mechanical Arm that tracks and mimics hand and arm gestures that does not require hand contact and touching controls by using Leap Motion Controller. In can provide more precision and control for additional efficiency.
The research attempted to determine the design of the robotic arm and how the Leap Motion Controller be integrated considering the features of the desired hand movement. It is also undertaken to evaluate the performance of the prototype considering the accuracy of the arm movement and response of the prototype and to address the problems encountered in the development of the study. The creation of the prototype was held as Pias, Mapandan, Pangasinan, while the testing procedures was conducted at Nancayasan, Urdaneta, Pangasinan.
To build the proposed study, the researchers used the Project Management Steps model of serve as a well-organized guide in doing the step-by-step process for the achievement of the different requirements of the study.
It is intended for the researchers to determine the accuracy of the arm movement through the calculation of the distance of the robotic arm from the initial point divided by the travelled distance of the human arm. The response of the prototype in terms of the shape and weight, reaction time and time required to move an object are also defined.
The manipulation of the robotic arm is made possible through Leap Motion Controller. It was found that the prototype is responsive in cubic, cylindrical, rectangular, and spherical objects weighing 0 to 200 grams given less than 10 seconds to move the object from point A to B with a distance of 30 centimeters. It takes approximately 262 milliseconds for the robotic arm react from the user's hand movement. Moreover, its accuracy percentage is equivalent to 86.46.
For the enhancement of the project, it is recommended to integrate wheels and/or mobile robot on the design to convert its static behavior into dynamic. To implement wireless control to the prototype, it is suggested to incorporate RF transceivers, Bluetooth, or Wi-Fi communication. It is also recommended to use 3D-printed robotic arm to improve grabbing mechanism and to properly exhibit hand movements.
Keywords: Engineering design; Robotics; Pangasinan